(untitled) (Journal of history, 2019)
The author describes the presence of more than 20 states and tribal associations that existed on the territory of Kazakhstan from ancient times until the middle of the fifteenth century, which played an important role in the process of formation of the Kazakh Khanate, as the author claims that the Kazakh Khanate is the legal successor of these states and tribal association. During the period of the Kazakh Khanate from the fifteenth century to the middle of the XVIII century, the author highlights the existence of several stages of Khan’s . The author gives a brief description of each stage, and highlights their features. The author also dwells on the process of formation of the Kazakh Khanate. Thus, the author highlights the importance of development of Khanate, in the context of the history of Kazakhstan